PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS POWER POINT UNTUK MENINGKATKAN RETENSI PESERTA DIDIK AUTIS - Marisa; Putri, Cendana Kusuma (Prosiding Temu Ilmiah Nasional Guru, 2023)
This research aims to measure the effectiveness of using power point multimedia-basedlearning media for students with special needs. The characteristics of autistic students who find itdifficult to focus require special treatment in learning. The use of multimedia-based learningmedia can provide a varied and attractive appearance so that it can invite students to take part inthe learning process. The research method was carried out using a qualitative method by observingstudents using power point-based multimedia. Data before and after the use of PowerPointmultimedia-based learning media were compared to see students' learning progress. The findingsfrom this research are that students more easily remember learning material through multimediapower points